Measurement of Hypothalamic Glucose Under Euglycemia and Hyperglycemia by MRI at 3T. Issue 3 (12th July 2016) - Joers, James M.; Deelchand, Dinesh K.; Kumar, Anjali; Moheet, Amir; Seaquist, Elizabeth; Henry, Pierre‐Gilles; Öz, Gülin
Abstract : Purpose: To evaluate the feasibility of using a clinical magnetic resonance (MR) system and MR spectroscopy (MRS) to measure glucose concentration changes in the human hypothalamus, a structure central to whole‐body glucose regulation. Subjects and Methods: A time series of MR spectra (semi‐LASER, TE = 28 msec), localized to the bilateral hypothalamus (∼1.6 ml) were obtained at 3T in six healthy subjects at baseline (euglycemia) and during a ∼65–70‐minute‐long hyperglycemic clamp in 11‐minute blocks with interleaved T 1 FLASH images to retrospectively assess head motion, and track changes in cerebrospinal fluid (CSF) partial volume. The LCModel was used to quantify the sum of glucose and taurine concentrations, [Glc+Tau], along with their associated Cramér‐Rao lower bounds (CRLB). Results: Spectral quality allowed quantification of [Glc+Tau] (sum reported due to high negative correlation between these metabolites) with CRLB <25% in 35/36 timepoints during hyperglycemia. Increased [Glc+Tau] was observed with hyperglycemia in all subjects, but most reliably in those with plasma glucose targets ≥300 mg/dl. For these subjects, [Glc+Tau]baseline ( n = 4) was 1.5 (±0.3, SD) mM, and increased to 4.5 (±1.1) mM ( n = 16) for timepoints acquired ≥25 minutes after onset of the clamp, with 15/16 timepoints having no overlap of 95% confidence intervals (CIs) between baseline and hyperglycemia. Preliminary analysis revealed a linear (1:5) relationship between hypothalamus–blood glucose concentrations. Conclusion: It is feasible to measure glucose concentration changes in the human hypothalamus using a standard 3T scanner and a short‐echo semi‐LASER sequence by utilizing retrospective motion tracking, CSF correction, predetermined quality acceptance criteria, and hyperglycemic blood glucose levels ≥300 mg/dl. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:681–691.